Optical observations of supernova 2012aw. Issue Volume 9:Issue S296(2013) (29th January 2014) - Bose, Subhash; Kumar, Brijesh; Sutaria, Firoza; Roy, Rupak; Kumar, Brajesh; Bhatt, Vijay K.; Chakraborti, Sayan
Abstract: We present optical UBVRI photometric and low-resolution spectroscopic follow-up observations of a type II SN 2012aw in a nearby (~10 Mpc) galaxy M95 during 4 to 270 days post-explosion. The evolution characteristics of optical brightness and color are found to have striking similarity with the archetypal type IIP SN 1999em. The mid-plateau M V is −16.7 mag and the ejected nickel mass is ~0.06 M⊙ . The presence and evolution of optical spectral features during 7d to 104d are also similar to SN 1999em as well as other normal type IIP events. The mid-plateau photospheric velocity is around 4200 km s −1 which is same as that of SN 2004et at similar phases, indicating similar energy of explosion i.e. 2 × 10 51 erg s −1 .